A cross-sectional study of caregiving tasks and mental health outcomes among diverse family dementia caregivers. - Johnson, Florence; Veliz, Philip; Boddakayala, Namratha; Ratliff, Hannah; Robinson-Lane, Sheria (Geriatric Nursing, 2026)
• Feeding assistance linked to the highest anxiety risk in Black caregivers. • Bathing assistance significantly increases anxiety in Black caregivers. • Study emphasizes need for culturally responsive caregiver support. • The emotional burden of caregiving tasks affects mental well-being. Black and Hispanic family caregivers (CGs) provide 83% of care for individuals with dementia in their communities, while often facing higher burdens and limited support. This study examined how specific caregiving tasks, such as activities of daily living (ADLs) and instrumental activities of daily living (iADLs), are associated with symptoms of anxiety and depression among Black and Hispanic CGs, using White CGs as the reference group. This cross-sectional secondary data analysis of 947 CGs aged 18 and older from the 2015 National Study of Caregiving (NSOC) was linked with the National Health and Aging Trends study (NHATS) data. Multivariable logistic regression modeling was used to assess the association between caregiving tasks and mental health, stratified by each race. The sample was predominantly female (65%), with a mean age of 57 (SD 20.05). Black CGs assisting with feeding (ADL) had significantly higher odds of anxiety (aOR = 2.02, 95% CI = [1.08, 3.75]) and depressive (aOR = 2.45, 95% CI = [1.25, 4.78]) symptoms compared to White CGs, anxiety (aOR = 1.45, 95% CI = [0.89, 2.35]) and depressive (aOR = 1.21, 95% CI = [0.78, 1.88]) symptoms. No significant associations between individual ADLs and iADLs and symptoms of anxiety or depression were observed in Hispanic CGs. Feeding and bathing tasks are associated with poorer mental health in Black CGs. Though results highlight the need for culturally responsive CG support; causal relationships cannot be made. Longitudinal research is recommended to better understand these associations before interventions are developed.